"HEAT AND MASS TRANSFER IN A VERTICAL CHANNEL THROUGH POROUS MEDIUM: INFLUENCE OF RADIATION AND SLIP CONDITIONS" - Kankanala Sharada, S Rakmaiah (Utilitas Mathematica, 2024)
This study numerically investigates simultaneous heat and mass transfer in a vertical channel filled with a porous medium, using a viscous, incompressible, and radiating fluid. The governing equations for heat and mass transfer are solved using an efficient finite-difference scheme to solve the ordinary differential equations. The study evaluates velocity, temperature, concentration, heat transfer rate, and mass transfer rate for various parameters, including magnetic field strength, suction, and slip conditions. Significant effects of magnetic field and suction parameters on fluid flow, heat transfer, and mass transfer characteristics are observed in the studied configuration. Additionally, for Bi > 0, an increase in the radiation parameter results in higher skin-friction values and lower Nusselt numbers.